Role of ultrasound-guided brachiocephalic venous cannulation for difficult venous cannulation in pediatric patients: A narrative review - Poonam Kumari; Amarjeet Kumar; Chandni Sinha; Ajeet Kumar; Kunal Singh (Journal of Anaesthesiology Clinical Pharmacology)
Difficult venous access is characterized by non-visible and non-palpable veins; a highly experienced operator is required with the use of technological aids to insert a vascular device. Patients with difficult venous cannulation undergo multiple, painful attempts to gain peripheral venous access. Compared to adults, inserting a central venous cannulation (CVC) is thought to be a more difficult procedure in children, particularly in neonates and young infants. IJV catheterization is perceived as the gold-standard route for CVC but remains difficult for newborn, premature, and critically ill children. Therefore, in recent years, novel ultrasound-guided brachiocephalic venous (BCV) cannulation in neonates has gained popularity. The aim of this narrative review was to assess the success rate. The primary objective of this review was to determine the first-attempt success rate. The secondary objectives were the total number of attempts, cannulation time, overall success rate, and complications. All articles relevant to BCV cannulation were searched in six major databases (PubMed, Embase, Medline, Ovid, PMC, and Google Scholar). A total of 16 records were included in this narrative review. According to Breschan et al., Merchaoui et al., and Vafek et al., the success rate of BCV cannulation in children was 89.1%, 98.4%, and 50%, respectively. Kumar et al., Erroz et al., and Breschan et al. found that the first-attempt success rate was higher in the in-plane left BCV (74%, 73% and 82.9% respectively). Falay et al. and Erroz et al. found a lower complication and infection with BCV cannulation. There is evidence that during CVC placement, US-guided BCV cannulation has a higher first-attempt success rate, requires less cannulation time, and has a lower complication rate in comparison to other approaches.